2006
DOI: 10.1146/annurev.publhealth.27.021405.102124
|View full text |Cite
|
Sign up to set email alerts
|

ENVIRONMENTAL JUSTICE: Human Health and Environmental Inequalities

Abstract: ▪ Abstract  In this review, we provide an introduction to the topics of environmental justice and environmental inequality. We provide an overview of the dimensions of unequal exposures to environmental pollution (environmental inequality), followed by a discussion of the theoretical literature that seeks to explain the origins of this phenomenon. We also consider the impact of the environmental justice movement in the United States and the role that federal and state governments have developed to address envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
495
1
9

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 833 publications
(522 citation statements)
references
References 61 publications
(46 reference statements)
17
495
1
9
Order By: Relevance
“…As one might expect, the more-deprived Cluster 9 has much higher levels of off-road diesel emissions, 7.91 (6.53, 9.27), compared to the less-deprived Cluster 7, 1.29 (1.26, 1.33). However, the more-deprived Cluster 9 has lower levels of NO 2 21.77) for Cluster 8, despite differences in poverty levels. Therefore, while it might be generally true that increased poverty is associated with increased air pollution exposures, the nature of these associations in Los Angeles County is complex and nonlinear.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…As one might expect, the more-deprived Cluster 9 has much higher levels of off-road diesel emissions, 7.91 (6.53, 9.27), compared to the less-deprived Cluster 7, 1.29 (1.26, 1.33). However, the more-deprived Cluster 9 has lower levels of NO 2 21.77) for Cluster 8, despite differences in poverty levels. Therefore, while it might be generally true that increased poverty is associated with increased air pollution exposures, the nature of these associations in Los Angeles County is complex and nonlinear.…”
Section: Resultsmentioning
confidence: 93%
“…These disparities translate into higher rates for mortality, morbidity, and disability for the lower SEP groups and people of color. 2 Although these health disparities are frequently attributed to individual health behaviors such as smoking, individual factors account for only a fraction of the overall inequalities between these groups. 3 As such, social epidemiology research has focused on the effects of SEP on many health outcomes, differential access to health and social services, 4 and neighborhood or community characteristics that may promote or adversely affect health.…”
Section: Introductionmentioning
confidence: 99%
“…Public health researchers have identified environmental pollution as a major contributor to health inequities (Brulle & Pellow 2006). Howie et al's (2005) review of thirteen Australian studies found adverse health effects of air pollution in major cities, but also identified gaps in knowledge, such as the spatial effects of air pollution, disentangling the health effects of different air pollutants, and assessing the interactive effects of air pollution with other environmental factors (Howie et al 2005, p.32).…”
Section: Environmental Injustice and Health Inequitymentioning
confidence: 99%
“…Howie et al's (2005) review of thirteen Australian studies found adverse health effects of air pollution in major cities, but also identified gaps in knowledge, such as the spatial effects of air pollution, disentangling the health effects of different air pollutants, and assessing the interactive effects of air pollution with other environmental factors (Howie et al 2005, p.32). Brulle and Pellow (2006) assert that while US studies emphasise community characteristics as determinants of health disparities, there are few that examine the role of exposures to toxic pollution on community health. Braveman (2006) Residents most likely to experience worse health or be exposed to greater health risks include people from disadvantaged social groups (such as poor, racial or ethnic minorities), women, or others discriminated against (Braveman 2006), such as those living close to polluting industries.…”
Section: Environmental Injustice and Health Inequitymentioning
confidence: 99%
“…Moreover, living within 200 metres of a major road is considered a potential risk to cardiovascular health (Brugge et al, 2007;Rioux et al, 2010), and for the development of asthma McConnell et al, 2006) and lung development deficits among children (Gauderman et al, 2007). Previous studies have argued that the combination of socioeconomic inequalities and exposure to air pollutants contributes to physiological vulnerability among members of low-income households (Brulle and Pellow, 2006;Kohlhuber et al, 2006;O'Neill, 2007). Other studies have noted that the health impacts of pollution are greater among children and the elderly.…”
Section: Introductionmentioning
confidence: 99%